The Insect Community on the Soil Surface - Harsimran K. Gill; Robert McSorley; Lyle Buss (EDIS)
It’s easy to find and collect insects, related arthropods, and other invertebrates from the soil surface using simple materials that are readily available. This 7-page fact sheet describes several collection methods and introduces common invertebrates that are found on the soil surface in agricultural fields and gardens in Florida. It was written by Harsimran K. Gill, Robert McSorley, and Lyle Buss, and published by the UF Department of Entomology and Nematology, January 2011.